1991
DOI: 10.1071/ea9910139
|View full text |Cite
|
Sign up to set email alerts
|

The relationships between liveweight, growth from weaning to mating and conception rate of Bos indicus cross heifers in the dry tropics of north Queensland

Abstract: Factors influencing the conception rates of 1332 Bos indicus cross maiden heifers in the dry tropics of North Queensland were studied between 1973 and 1986. The heifers, which were 112 and 314 Bos indicus (Brahman or Sahiwal) crosses with Bos taurus, were mated at 24-27 months of age over a 3-month period commencing in mid to late January. The effects of liveweights and growth rates on conception rate were initially assessed in separate models which always included cohort (year of branding group) as an additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…Overall, the parameter that explained the greatest variation for occurrence of pregnancy was PM.LW, which was, in general, greater for the NW compared with EW heifers. This is consistent with previous studies which have found that the most important factor affecting pregnancy rates of maiden heifers is PM.LW [ 35 , 36 ]. This outlines the long-term consequence of first dry season supplementation and WW on pregnancy percentage, a practical objective of this experiment.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Overall, the parameter that explained the greatest variation for occurrence of pregnancy was PM.LW, which was, in general, greater for the NW compared with EW heifers. This is consistent with previous studies which have found that the most important factor affecting pregnancy rates of maiden heifers is PM.LW [ 35 , 36 ]. This outlines the long-term consequence of first dry season supplementation and WW on pregnancy percentage, a practical objective of this experiment.…”
Section: Discussionsupporting
confidence: 93%
“…The authors proposed a target LW (curfew) of 253 kg measured in October/November would result in an 80% of pregnancy for two-year-old heifers. Similarly, working with two-year-old Brahman cross heifers Doogan et al [ 36 ] et al proposed approximately 270 kg as a target LW at the start of mating (January) in order to achieve a 80% confirmed pregnancy at the end of a 100-day mating period…”
Section: Discussionmentioning
confidence: 99%
“…Body mass and body condition therefore undergo oscillating patterns of increase during the wet season and decrease during the dry season (Holroyd et al, 1979). The severity of weight loss and decrease in condition have major effects on reproductive performance, with degree of weight loss during the preceding dry season and condition at mating correlating with conception rates in both heifers and mature cows (Doogan et al, 1991; O'Rourke et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…There are in turn a range of factors associated with age of puberty including live weight, body condition score and breed (e.g. Doogan et al 1991); b) Post partum anoestrus interval, the time between calving date and when the cow recommences cycling, influenced by live weight, body condition score and breed, as well as lactation status; c) Time of conception after calving (e.g.…”
Section: Condition Scorementioning
confidence: 99%